Defining high-risk pregnancy: Protocol for a systematic scoping review of clinical determinants, complications, and adverse birth outcomes - Xiali Yang; Xin Wee Chen; Philip R. A. Baker (PLoS ONE, 2025)
Introduction Accurately identifying clinical determinants within the medical paradigm is essential for evidence-based planning and management of high-risk pregnancies, and for preventing adverse birth outcomes through targeted interventions. However, a systematic synthesis of regional classification systems, risk factors, complications, and adverse birth outcomes associated with high-risk pregnancies remains lacking. Objective This study protocol aims to systematically identify relevant published research, assess the risks of bias, and summarize the routinely collected clinical determinants/data used in classifying high-risk pregnancy status and the relationship of this status with its complications. Methods and analysis The bibliographic databases of Cochrane Library, Web of Science, CNKI, SCOPUS, and PubMed-MEDLINE will be searched for observational studies without language restrictions. The two-stage screening process will be conducted, involving independent full-text reviews, risk of bias assessments, and data extraction by two reviewers. Narrative synthesis will address selective publication bias using established critical appraisal and evidence evaluation methods. Study selection and reporting will adhere to the PRISMA-P guidelines. Ethics and dissemination Ethics approval is not required, as this systematic review utilises only published data. The findings will be disseminated through publication in a peer-reviewed journal and presentation at conferences. Protocol registration PROSPERO database registration (registration number: CRD420251026327).